(untitled) (Revista de História da UEG (REVHIST), 2020)
Abstract: This work presents an analysis focused on the role of the instrumentalist-composer as an element that unites the cultures characterized as "erudite" and "popular" in the different practice spaces of Brazilian and South-Rio Grande Choro. Firstly, the relationship between popular and scholarly cultures is approached, seeking to reveal the existing interaction, non-opposition, and dispute for importance and hierarchy of concepts that, through the performance of the instrumentalist-composer, becomes characteristic of the history of the genre. In the second part of the work, the role of the instrumentalist-composer is highlighted in the debate, highlighting his contribution and importance as a mediator of these multicultural spaces of practice in different historical moments and with examples similarly contextualized in the scenario of national and southern Rio-Grandense Choro.Keywords: Choro. History. Popular Culture. Erudite Culture. Rio Grande do Sul.